Nilai-Nilai Religius Islam dalam Novel Bidadari Berbisik Karya Asma Nadia - Rasmalina Putri; Noni Andriyani (UIR Press, 2022)
This research is motivated by the research problem of how the religious values ​​of Islam in the novel Bidadari Whispering by Asma Nadia. In terms of language, storyline, story content. The method used in this research is descriptive. This research is included in qualitative research. The results of this study are the sources of data used in the novel Bidadari berbisik by Asma Nadia. This novel was published in Jakarta, Republika publisher in February 2020. The number of pages is 301 sheets, and there are 5 chapters. This research uses hermeneutic technique. The author interprets the data based on the data analysis conducted on Islamic religious values ​​in the novel Bidadari Berbisik by Asma Nadia. There are 61 data in this study including , 1. Faith (tawhid) found 25 data, 2. Norms of Life (fiqh) found 5 data, 3. Attitude and behavior (morals) found 31 data. The data that is more dominant in the novel Bidadari Whispering by Asma Nadia is behavioral attitudes (morals) as many as 31 data.